PENGEMBANGAN VIDEO ANIMASI DAPAT MENINGKATKAN PENGETAHUAN PENCEGAHAN KARIES GIGI PADA ANAK SEKOLAH DASAR (Jurnal Kesehatan Siliwangi, 2021)
Background: Dental caries is a dental and oral disease that mostly affects children under the age of 12 years. Prevention of dental caries can be done by brushing teeth 2 times a day, avoiding sweet foods, using a soft-bristled toothbrush, eating vegetables and fruit. Purpose: Develop an animated video media regarding the prevention of dental caries in elementary school children that can be used in dental health education. Methods: The research method used is exploratory sequential mixed method, starting with qualitative research and then the second stage is quantitative research. The data of this study came from the results of in-depth interviews with 7 students, then a media feasibility assessment was carried out by 2 experts and 67 students, then the results of the pretest posttest questionnaire were distributed to 67 students. Knowledge data was processed using the Paired T-test. Results: the original average of 6.69 to 9.52 and animation video media is feasible to use, judging by the results of the assessment of media experts getting a score of 85% including very feasible criteria, material expert assessments getting a score of 100% including very feasible criteria, and user ratings get a score of 79.1% including eligible criteria. Conclusion: The animated video media for preventing dental caries is very feasible as a medium of information. The author proposes a recommendation that animated video media can be used as a medium of learning for elementary school children.